Kinome multigenic panel identified novel druggable EPHB4‐V871I somatic variant in high‐risk neuroblastoma. Issue 11 (26th April 2020) - Andolfo, Immacolata; Lasorsa, Vito A.; Manna, Francesco; Rosato, Barbara E.; Formicola, Daniela; Iolascon, Achille; Capasso, Mario
Abstract: Neuroblastoma (NB) is the most common extracranial neoplasm in children. The overall outcome for high‐risk NB patients is still unacceptable, therefore, it is critical to deeply understand molecular mechanisms associated with NB, which in turn can be utilized for developing drugs towards the treatment of NB. Protein kinases (TKs) play an essential role in the regulation of cell survival and proliferation. Different kinases, such as anaplastic lymphoma kinase (ALK), Aurora kinase, RET receptor tyrosine kinase, are potential therapeutic targets in various cancers, including NB. We analysed a cohort of 45 high‐risk NB patients and 9 NB cell lines by a targeted—(t)NGS custom gene panel (genes codifying for the kinase domains of 90 TKs). We identified somatic variants in four TK genes ( ALK, EPHB4, LMTK3 and EPHB6 ) in NB patients and we functionally characterized an interesting somatic variant, V871I, in EPHB4 gene. EPHB4 plays a crucial role in cardiovascular development and regulates vascularization in cancer‐promoting angiogenesis, tumour growth and metastasis. Several EPHB4 mutations have previously been identified in solid and haematological tumour specimens but EPHB4 mutations were not described until now in NB. Interestingly, a re‐analysis of public CGH‐array showed that the EPHB4 gain is associated with advanced diseases in NB. We further demonstrated that higher EPHB4 expression is correlated to stage 4 of NB and with poor overall survival. Additionally, we also revealed that the EPHB4‐V871I accounts for increased proliferation, migration and invasion properties in two NB cell lines by acting on VEGF, c‐RAF and CDK4 target genes and by increasing the phosphorylation of ERK1‐2 pathway. The use of two EPHB4 inhibitors, JI‐101 and NVP‐BHG712, was able to rescue the phenotype driven by the variant. Our study suggested that EPHB4 is a promising therapeutic target in high‐risk NB.